1990
DOI: 10.1002/prep.19900150202
|View full text |Cite
|
Sign up to set email alerts
|

Combustion of Black Powder. Part 1: Thermo‐analytical studies

Abstract: An experimental programme is described, in which a number of thermo‐analytical techniques, differential scanning calorimetry (DSC), thermogravimetry (TG and DTG) are applied to investigate the combustion of black powder. The primary aim has been to investigate, and determine qualitatively and quantitatively, the nature of the solid products of combustion. Additionally, standard analytical techniques were applied, to a chemical analysis of the solid products, resulting from the electric arcignition of a sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 6 publications
2
22
0
Order By: Relevance
“…The first could be due to the oxidation of free S by NaC104 in the presence of charcoal whereas the broad peak at 355 ~ could be due to the oxidation of adsorbed S [9]. There was no such exothermic reaction between NaCIO4 and Safter or prior to the melting of NaC104 in case of a binary mixture of NaC104 and S (75:25) as evidenced in the case of KNO3 [1,10]. In the HSM it was also observed that during heating of this binary mixture all of the yellow sulphur just evaporated leaving white NaC104 crystals thus showing no reaction between S and NaCIO4 similar to KC104 [5].…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…The first could be due to the oxidation of free S by NaC104 in the presence of charcoal whereas the broad peak at 355 ~ could be due to the oxidation of adsorbed S [9]. There was no such exothermic reaction between NaCIO4 and Safter or prior to the melting of NaC104 in case of a binary mixture of NaC104 and S (75:25) as evidenced in the case of KNO3 [1,10]. In the HSM it was also observed that during heating of this binary mixture all of the yellow sulphur just evaporated leaving white NaC104 crystals thus showing no reaction between S and NaCIO4 similar to KC104 [5].…”
mentioning
confidence: 88%
“…As some of the water from the sample preparation stage is retained by NaC104, the ignition with nichrome wire [1,5] was not so abrupt as in the case of KC104 [5]. However, if the ternary mixture is heated to 95 ~ first, then ignition by nichrome wire produces a sudden flash.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The combustion of black powder [1][2][3] which has a traditional composition of KNO3 (75%), charcoal (15%) and S (10%) [4][5] has been studied in our laboratories. Although black powder is the oldest explosive known, it is still being used due to its peculiar properties [6].…”
mentioning
confidence: 99%